The Prevention of Underage Marriage in Indonesia: State, Religious Authority and Human Rights - Asfa Widiyanto; Siti Zumrotun; Heru Saputra (Justicia Islamica, 2024)
This paper strives to investigate dynamic interplays among the state, religious authority, and human rights surrounding early marriage among Muslims in contemporary Indonesia. More specifically, this paper will address the following problems: (a) how do religious authorities respond to the cases of early marriage in Indonesia; (b) what kind of religious understanding should be developed to prevent early marriage in Indonesia; (c) how do religious judges exert their agency in preventing early marriage in Indonesia amidst the pressure of state, religion, and human rights. This research employs a qualitative methodology, including interviews with religious scholars and judges and analyzing legal documents. The finding of the research states that while some religious authorities advocate early marriage based on conservative interpretations, progressive scholars argue for delaying marriage to safeguard children's health and rights. In addition, a more context-sensitive understanding, rooted in maqasid al-sharia (objectives of Islamic law), is essential for preventing early marriage. Religious judges, meanwhile, play a pivotal role in navigating social, legal, and religious pressures, especially in cases involving pre-marital pregnancies in Indonesia. This study contributes to the sociology and politics of Islamic law, most notably in unravelling the complexity of power relations among the state, religious authority, and human rights regarding underage marriage.